Direito à educação e ampliação da escolaridade obrigatória em Ponta Grossa (2001 – 2008) - Flach, Simone de Fátima (2010)
The work presented here analyses the impact that the process whereby the compulsory education period was extended from 8 to 9 years had on the state of Paraná, focusing on the political and educational conditions of the city of Ponta Grossa in the period between 2001 and 2008. The general purpose of this investigation was to point out the effects such change had on the lives of the citizens of Ponta Grossa, taking into account the government‟s commitment to allow every child the right to have access to education (nursery education for children below 6 years, and primary education for children above that age). The investigation sought to identify the link between the city education policy and broader social, political and historical influences and determinations, aiming to show that there is a dialectical movement between the particular and the universal. The research was developed through the observation and experience of the effects of the educational policy concerned in daily classroom practice and social life. In order to understand the effects produced in people‟s real lives, it was necessary: to carry out a historical and statistical survey based on the official documents and records available; to follow the discussions related to the extension of the compulsory education period at city, state and national levels, by carrying out a survey of norms and recommendations issued by normative and legislative bodies, according to records from the City Education Board of Ponta Grossa; to take part in public hearings held by the legislature of Paraná and follow the discussions and decisions of the state judiciary; to carry out a particular study on the historical formation of compulsory education as well as on the related political agenda at local, state, national and international levels; and finally to achieve a better knowledge on the guarantee of both the right to education and the respect to Brazilian citizens. The central point of the discussion is the importance of guaranteeing people the right to education, rather than it just being prescribed by law, because this initiative not only shows people being acknowledged by the government but is fundamental to allow them to have access to the means by which their citizenship is enhanced. The conclusion reached by the research is that the political actions analysed and their effects have been weak and incomplete; furthermore, the right to education for Brazilian citizens living in Ponta Grossa, Paraná, is in a contradictory situation in which social, economic and cultural interests are elements dialectically involved in the political and intellectual struggle occurring within the places where the procedural steps for public education policies are taken. The scientific merit of this research is to open the black box of the policy of the extension of the compulsory education period and allow its effects to be known and analysed. Particularly, the information presented here contributes to raising individual and collective awareness about how citizens‟ right can be violated by means of apparently correct and well-intentioned measures.